помогите пожалуйста решить уравнение: 3*(-0,1х+7)-5*(0,3х-3)=0

4*(5х+4)-(11х-23)=3

2

Ответы и объяснения

2013-05-10T19:55:48+00:00

 

3*(-0,1х+7)-5(0,3х-3)=0

-0,3х+21-1,5х-15=0

-0,3х+1,5х=21-15

1,8х=6

х=6:1,8

х=3,3

 

 4(5х+4)-(11х-23)=3

20х+16-11х-23=3

20х+11х=16+23-3

9х=36

х=36:9

х=4

 

 

 

 

 

 

 

 

 

 

Лучший Ответ!
2013-05-10T20:06:12+00:00

3*(-0,1x+7)-5*(0,3x-3)=0
-0.3x+21-1.5x+15=0

-1.8x+36=0

x=36/1.8

x=20

 

4*(5х+4)-(11х-23)=3

20x+16-11x+23-3=0

9x+36=0

x=-36/9

x=-4